PENGARUH MUSIC MOVEMENT THERAPY TERHADAP KEMAMPUAN AKTIVITAS HARIAN PADA PASIEN STROKE DI RSUP. PROF. DR. R.D. KANDOU MANADO - Andreas Rantepadang; Angelia Tendean (Jurnal Skolastik Keperawatan, 2019)
ABSTRACT Introduction: Stroke is a condition of circulatory disorders that results in changes in brain function. Stroke results in a decrease in the ability of daily activities that affect the quality of life of stroke patients. Good handling can prevent complications and improve the ability of daily activities of stroke patients. Purpose: The purpose of this study is to identify the effect of music movement therapy (MMT) on the ability of daily activities of stroke patients in RSUP. Prof. Dr. R.D. Kandou Manado. Method: Quasi experiment one group pretest and posttest method. Determination of the sample using consecutive sampling technique, 65 respondents were given standard hospital handling and MMT 5 times a week (30 minutes each therapy) for two weeks. Results: The results showed that the patient's daily activity ability before intervention was 47.7% in total dependence, very dependent on 46.2%, partial dependence at 4.6% and slightly dependent on 1.5% while the ability of daily activities after MMT intervention was very dependent 5%, partial dependence 26.2%, independent 24.6%, total dependence 7.7% and slightly dependent 3.1%. The Wilcoxon test showed the effect of MMT on the daily activity ability of stroke patients (p-value 0.000). Discussion: This study recommends the use of MMT as a basis for consideration for alternative therapies in improving the ability of daily activities of stroke patients. Keywords: Music, movement, therapy, daily activities.